2022
DOI: 10.3389/fphar.2021.745683
|View full text |Cite
|
Sign up to set email alerts
|

Crocetin: A Systematic Review

Abstract: Crocetin is an aglycone of crocin naturally occurring in saffron and produced in biological systems by hydrolysis of crocin as a bioactive metabolite. It is known to exist in several medicinal plants, the desiccative ripe fruit of the cape jasmine belonging to the Rubiaceae family, and stigmas of the saffron plant of the Iridaceae family. According to modern pharmacological investigations, crocetin possesses cardioprotective, hepatoprotective, neuroprotective, antidepressant, antiviral, anticancer, atheroscler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 185 publications
(160 reference statements)
0
26
0
1
Order By: Relevance
“…The safety of saffron and its metabolites have been evaluated in clinical trials of both adult and pediatric patients, administered mainly p.o. , in different dosages or formulations (14–450 mg of saffron, 5–30 mg of CRCs, or 7.5–37.5 mg of CRT) [ 143 , 144 , 145 ]. Administration of Crocus sativus L. stigma tablets (200 and 400 mg/day, for 7 days) in healthy adult volunteers, was safe, without significantly affecting any hematological, biochemical and coagulation parameters [ 146 , 147 , 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…The safety of saffron and its metabolites have been evaluated in clinical trials of both adult and pediatric patients, administered mainly p.o. , in different dosages or formulations (14–450 mg of saffron, 5–30 mg of CRCs, or 7.5–37.5 mg of CRT) [ 143 , 144 , 145 ]. Administration of Crocus sativus L. stigma tablets (200 and 400 mg/day, for 7 days) in healthy adult volunteers, was safe, without significantly affecting any hematological, biochemical and coagulation parameters [ 146 , 147 , 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…423 The carotenoid crocetin is a 20-carbon natural carotenoid which is also a diterpenoid and a vitamin A analog. 424 Kordzadeh et al identified it as a candidate drug for COVID-19 treatment based on its high binding energies to S protein and M pro of SARS-CoV-2 virus. 425 Further, in a phase I/II clinical trial on COVID-19 patients suffering from severe respiratory complications, a single injection of LEAF-4L6715 (a liposomal nanocarrier encapsulating crocetin) enhances the oxygenation of vascular tissue and therefore has the potential to improve the clinical outcomes of ARDS and COVID-19 in severely impacted patients.…”
Section: Structures Of Small Molecule Drugs For Covid-19 Therapymentioning
confidence: 99%
“…Many of them are predicted to be GT198 inhibitors and can be tested in the future. These include saffron ( 70 , 71 ), pinellia ternate ( 72 ), ephedra ( 73 , 74 ), rhubarb ( 75 ), pomegranate ( 76 78 ), arisaematis rhizome ( 79 ), cuttlefish bone ( 80 , 81 ), gardenia ( 82 ), houttuynia cordata ( 83 ), loquat leave ( 84 ), mistletoe ( 85 87 ), Nong Ji Li ( 88 ), plantain peel ( 89 91 ), radix platycodonis ( 92 ), snakegourd ( 93 ), soursop leave ( 94 , 95 ), turmeric ( 96 , 97 ), Wu Gu Teng ( 98 ) ( Table 1 ). This collection represents only examples but is far from an inclusive or exhaustive list.…”
Section: Oncoprotein Gt198 As Drug Targetmentioning
confidence: 99%